Potency of sunscreen of cinnamat and benzophenon combination in various concentrations - Dewi Martini, Dewi Martini (Universitas Gadjah Mada, 1995)
This study was aimed at determining the effect of dilution of active ingredients of chemical sunscreen consisting of octyl-methoxy cinnamate and benzophenon-3 on its potency, in terms of SPF (sun-protection factor) and APF (UV-A protection factor).Factors of sun & UV-A protection factor had been tested in the Laboratory of Photobiology, Department of Dermato-Venereology Dr. Sardjito General Hospital Yogyakarta, involving 45 people who were voluntarily participating in the study of sun-protection Factor and 22 people in the study of UV-A protection factor.The results showed that there was a significant correlation between APF of the chemical sunscreen and dilution of the active ingredients, but unseen for SPF. No differences in the potency of cream and lotion sunscreens. Based on this study, it is recommended that all concentration of these sunscreens can be used by Indonesians.Key words : cinnamate - benzophenon - sunscreen - sun protection factor - UV-A protection factorÂ